The methods of anticipating the family problems at the Sharjah Police Headquarters: An Analytical Study - AlKetbi, Huwaiden Mohamed; Alhalalat, Khalil Ibrahim (Al-Adab Journal, 2023)
The aim of this research is to identify the methods of anticipating family problems at the Sharjah Police Headquarters through an analytical study, clarifying the anticipating the future of family problems and the most important approaches followed in the anticipating process, and revealing ways to anticipating the future of family problems in the Sharjah Police Headquarters, and an explanation of the scenarios’ mechanism for the future of anticipating family problems in the Sharjah Police. It has become clear to us through this research that early action to confront family problems is considered as investment for the future, and that anticipating of family problems at the Sharjah Police Headquarters depends on a number of mechanisms and processes that enable people and institutions to collect information in organized ways and from multiple sources, such as linking between a set of new development approce in several sectors, in order to focuse in family problems from a holistic perspective to reduce the family problems. The Sharjah Police Headquarters seeks with several scientific and security methods, to search for the causes of family problems, in order to work on solving them and establish the appropriate foundations to eliminate them in right time. The researchers recommended the Sharjah Police Headquarters about the importance of continuing to provide preventive and curative programs for family problems directed to the family in the Emirate of Sharjah, and activating the role of the Department of Preventive and Remedial Programs in training counselors and trainers to improve the counseling role and keep pace with its developments to overcome the family problems in the Emirate of Sharjah.